KONFLIK DALAM NASKAH DRAMA TANPA PEMBANTU KARYA A.ADJIB HAMZAH : PENDEKATAN PSIKOLOGI SASTRA - Eka Purnamasari; YB Maridja (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to describe the nature of conflict, causes, and how to resolve conflict in drama Tanpa Pembantu. This type of research is qualitative research. Data collection technique is done by reading and recording the data obtained in the drama Tanpa Pembantu of A. Adjib Hamzah. Technique of data analysis of research done by qualitative descriptive technique. The result of the research shows that the form of conflict in this drama script is the jealousy and the difference of opinion, Yuliati jealous with Lisawati coming to his house, Yuliati thinks that her husband Sapari has an affair with Lisawati, the difference of opinion between Sapari and Yuliati makes the atmosphere heating up because each side feel the most right. The cause of conflict in the drama Tanpa Pembantu is freedom with freedom, freedom experienced by Yuliati because Yuliati does not take care of homework, whereas Sapari experiencing the non-liberation of parenting, the cooperation with the competition seen from the figure Sapari and Lisawati Sapari very appreciate Lisawati. Lisawati strongly disagreed with Yuliati's treatment of Sapari, the presence of implus expression caused by tension and anxiety, anxiety seen in the difference of opinion and the harsh contradictions made by Sapari and Yuliati figures in the face of a problem, Anxiety seen in Sapari figure, Sapari seen anxious, worried and anxious at the time of Lisawati's visit to her home. How to resolve the conflict based on the sequence of actions to be taken when solving the problem of approaching Lisawati's regretful character has left Sapari, dodging the Lisawati character who is about to approach again, approaching Yuliati's character who accuses Sapari of dating on campus.